Forest growth trends in the eastern United States - Craig Loehle (The Forestry Chronicle, 2020)
Changes over the past century in factors such as temperature, precipitation, fire regimes, ozone, atmospheric CO2, and nitrogen deposition naturally lead to questions about forest growth over this same time period. Determining changes in forest growth over long intervals is complicated by constantly changing growth conditions due to tree maturation, stand self-thinning, disturbance, fires, and other factors. Because a comprehensive review is lacking, results were evaluated from publications examining forest growth trends in the eastern United States over the past 100 years. Available studies used multiple sources of data, including permanent plots, growth models, and tree-ring analysis to evaluate forest growth trends. Reviewed publications (n = 19) reported medium to strong growth enhancement based on a variety of data types over periods exceeding 100 years in some cases. Model-based analyses, which mostly did not include CO2 and nitrogen fertilization effects, had lower estimates of growth enhancement. Results were consistent for different study lengths and data types. No study reported forest-scale growth declines. Factors identified as the cause of enhanced growth varied by study, but included rising CO2 concentrations, N deposition, increased precipitation, and warming temperatures.